SOCIAL WELFARE AND FAMILY SUPPORT AS A DIRECTION OF HUNGARIAN SOCIAL POLICY (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The author investigates the transformation processes of family values, preconditions that have influenced the emergence of the familism in Hungarian society. The article deals with the analysis of the main characteristics of neo-familism as the dominant social phenomenon of the present, which directly impacts the Hungarian family policy and determines the further direction of the family support system formation. It has been noted that familism is a complex concept and can be interpreted from different perspectives. This term is revealed through the prism of personal and family values, norms, interpersonal and social relations, as well as governance systems strategies. In this article, familism is discussed mainly as a system of governance measures, disclosed through the demonstration of social, in particular, family policy strategies, as well as instruments of its regulation. Hungarian family policy and the effects of familism on it are described and analysed in several characteristics, such as types of financial support, supporting measures to facilitate parents' participation in the labour market and the social services systems. It is proved that, in comparison with other European Union countries, the parental support system of childcare in Hungary is one of the most comprehensive. On the basis of the analysis, it has been concluded that the Hungarian family support system was formed under the influence of the consequences of historical events and political ideologies. The key factors, which are determining the direction of the system transformation today, are both post-socialism and Europeanisation at the same time. The analysis of the historical preconditions of the family policy formation and its modern regulatory instruments classifies the Hungarian support system as optional familism, which provides universal financial support to families, a comprehensive system of parental leave and childcare allowances, tax deductions, public nursery and kindergarten services. The author also underlines the significance of analysing the Hungarian welfare system and social services which support not only families in difficult life circumstances but also middle-class families.
Keywords: familism, familisation, neo-familism, family policy, family support system, family values, family values transformation.